Penentuan Kerugian Keuangan Negara yang Dilakukan Oleh BPK dalam Tindak Pidana Korupsi - Ayu Astuti, Chandra; Chariri, Anis (Diponegoro Journal of Accounting, 2015)
This research aimed to understand the scope of financial state from the perspective of auditor. This study also aims to identify and describe the method of calculation that is calculated by supreme audit board to determine the financial state loss all this time. This study calculate state financial loss in term of tangible financial state loss and potential financial state loss.Informan used for this study are five auditors from supreme audit board that already did the calculation of financial state loss. The informan’s experience can describe how the calculation of financial state loss is currently conducted by auditors. In addition, this study also used documentation of technical documentation of investigative auditThe findings show that auditor perceived financial state loss as loss of money, securities and also goods that orginaly belong to state. The calculation of tangible financial state loss can be calculated by comparing the number of money that should be received or paid with the number that already being received or paid by the state. The calculation of potential financial state loss can be calculated with the same method as tangible financial state loss.